DEVELOPING CROSS-CULTURAL LEADERSHIP: A MIXED METHODS STUDY OF THAI BORDER SCHOOL ADMINISTRATORS - SINGKHAM, Rakpa; ATCHASIT, Ankinadana; KAJORNATTHAPOL, Pongwiritthon (Asian Administration and Management Review, 2026)
This study investigates cross-cultural leadership practices and professional development pathways of school administrators operating within Thailand’s complex, multicultural border region. Employing a robust mixed-methods sequential explanatory design, the research comprehensively evaluates critical leadership dynamics within the Mae Cha Rao School Group in Tak Province. The quantitative phase surveyed 62 administrators using a validated instrument measuring four core dimensions: transformational leadership, empathy in work practice, communication competence, and trust-building. Descriptive results indicated a high overall capacity for cross-cultural leadership, with empathy and trust-building as the most prominent strengths among school leaders. Conversely, communication competence ranked the lowest, revealing distinct operational challenges in successfully navigating linguistic boundaries and diverse community expectations. To address these specific gaps, the qualitative phase utilized structured interviews with five educational experts to formulate targeted, context-specific developmental strategies. Recommendations strongly emphasize continuous cultural immersion, empathy-based professional training, flexible bilingual communication channels, and the establishment of highly transparent administrative systems. Integrating these empirical findings demonstrates that effective management in diverse environments requires balancing emotional intelligence with systemic cultural adaptability to promote educational equity across ASEAN school systems.